1999
DOI: 10.1159/000026553
|View full text |Cite
|
Sign up to set email alerts
|

Auditory P50 in Schizophrenics on Clozapine: Improved Gating Parallels Clinical Improvement and Changes in Plasma 3-Methoxy-4-Hydroxyphenylglycol

Abstract: Schizophrenic patients have decreased inhibition of the P50 auditory evoked potential response to the second of two paired click stimuli delivered 500 ms apart. This deficit in inhibitory gating does not change during treatment with typical neuroleptics. We recently reported that neuroleptic-resistant schizophrenics had enhanced P50 gating after 1 month of clozapine treatment, if they responded with decreased clinical symptoms. This study reports the outcome of more prolonged treatment. Ten treatment-refractor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
68
0
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(71 citation statements)
references
References 41 publications
2
68
0
1
Order By: Relevance
“…Normal control participants normally exhibit suppression in the range of 50-70% , while it has been demonstrated that patients with schizophrenia display significantly lower P50 suppression (Adler et al, 1982;Boutros et al, 1991;Light et al, 2000;Ward et al, 1996;Yee and White, 2001;Braff et al, 2007), which is interpreted as reflecting a deficit in 'sensory gating' (Adler et al, 1982). Analogous to the PPI findings, there is also some evidence that P50 suppression deficits in schizophrenia may be normalized with the use of atypical antipsychotic drugs (Light et al, 2000;Nagamoto et al, 1996Nagamoto et al, , 1999Adler et al, 2004;Becker et al, 2004).…”
Section: Introductionmentioning
confidence: 80%
“…Normal control participants normally exhibit suppression in the range of 50-70% , while it has been demonstrated that patients with schizophrenia display significantly lower P50 suppression (Adler et al, 1982;Boutros et al, 1991;Light et al, 2000;Ward et al, 1996;Yee and White, 2001;Braff et al, 2007), which is interpreted as reflecting a deficit in 'sensory gating' (Adler et al, 1982). Analogous to the PPI findings, there is also some evidence that P50 suppression deficits in schizophrenia may be normalized with the use of atypical antipsychotic drugs (Light et al, 2000;Nagamoto et al, 1996Nagamoto et al, , 1999Adler et al, 2004;Becker et al, 2004).…”
Section: Introductionmentioning
confidence: 80%
“…Other studies reporting gating improvements with nicotine in rodents and humans, however, have found increases in S 1 but not S 2 (Crawford et al, 2002;Cromwell and Woodward, 2007;Metzger et al, 2007;Phillips et al, 2004Phillips et al, , 2007Rudnick et al, 2010). Clozapine, the prototype of the 'atypical' antipsychotics, and one of the few medications shown to reverse auditory sensory gating impairment in both schizophrenia and animal models, appears to selectively reduce S 2 -P50 responsivity via an α7 nicotinic mechanism (Simosky et al, 2003;Adler et al, 2004;Nagamoto et al, 1996Nagamoto et al, , 1999.…”
mentioning
confidence: 86%
“…Other studies reporting gating improvements with nicotine in rodents and humans, however, have found increases in S 1 but not S 2 (Crawford et al, 2002;Cromwell and Woodward, 2007;Metzger et al, 2007;Phillips et al, 2004Phillips et al, , 2007Rudnick et al, 2010). Clozapine, the prototype of the 'atypical' antipsychotics, and one of the few medications shown to reverse auditory sensory gating impairment in both schizophrenia and animal models, appears to selectively reduce S 2 -P50 responsivity via an α7 nicotinic mechanism (Simosky et al, 2003;Adler et al, 2004;Nagamoto et al, 1996Nagamoto et al, , 1999.Nicotine influences the release of not only acetylcholine, but also of dopamine (DA) and other neurotransmitters (norepinephrine, serotonin, glutamate, GABA) but it is not clear how these noncholinergic systems participate in gating. Although there is still confusion regarding the temporal sequencing of regionally specific DA changes in schizophrenia (Kellendonck et al, 2006), negative symptoms and cognitive deficits in this disorder have been linked to prefrontal hypodopaminergia while positive symptoms have been associated with striatal hyperdopaminergia (Kapur and Malmo, 2003).…”
mentioning
confidence: 92%
“…Studies have shown that the auditory gating improves in the DBA/2 mouse with nicotine administration [54], just as it does in schizophrenia patients [27]. Additionally, similar effects were found for clozapine in both the DBA/2 mouse [55] and schizophrenia patients [33]. The mechanism of auditory gating has been clarified through the use of these animal models.…”
mentioning
confidence: 90%
“…Relatives of people with schizophrenia also have poor P50 suppression without the confounds of the additional pathological effects of schizophrenia, the effects of medications or chronic smoking [29,30,31,32]. People with schizophrenia treated with clozapine exhibit normalization of their P50 ratio coincident with improvement in their clinical symptoms [33]. Clozapine, which releases acetylcholine in the hippocampus [34], may thereby indirectly act on the nicotinic cholinergic receptors to normalize the P50 ratio, as people with schizophrenia also decrease the amount of cigarettes they smoke while taking this medication [35,36].…”
mentioning
confidence: 99%